Aplikasi Monitoring Peralatan, Bahan Laboratorium Menggunakan Metode Sequential Search di Laboratorium Mikrobiologi dan Genetika UNAS - Chairil Rohadi; Iskandar Fitri; Nurhayati Nurhayati (KITA Institute, 2022)
The Faculty of Biology at the National University has a Microbiology and Genetics laboratory which is used for practicum activities, research, and fieldwork lectures. At the analysis stage, problems were found, namely in recording the use of equipment and materials used by students for research activities still using conventional methods, this resulted in delays in managing and conveying information. Adequate lecture facilities are an important aspect in helping the teaching and learning process. Based on the background of the problem, the author aims to make the equipment monitoring process more efficient, using Android-based devices. The author uses the Sequential search method in the process of monitoring equipment in the laboratory. This research was tested using black-box testing and white box testing by distributing questionnaires conducted using a Likert scale with a value range of 5 to 25 student correspondents with an average value for software testing = 4.6; Interface = 4.44; Software features = 4.32; item search feature = 4.08; with the final mean = 4.09.